Impact of Tremor on Patients With Early Stage Parkinson's Disease - Heusinkveld, Lauren E.; Hacker, Mallory L.; Turchan, Maxim; Davis, Thomas L.; Charles, David (Frontiers in Neurology, 2018)
Tremor is one of the most visible features of Parkinson’s disease (PD), and the majority of PD patients experience tremor during the course of the disease. However, the distress caused by this cardinal motor feature for patients early in the course of their PD is commonly underappreciated. People living with early stage PD often experience intense embarrassment and difficulties due to their tremor that limit social interactions, and tremor frequently interferes with the ability to perform activities of daily living and simple tasks at home and work. Although tremor is primarily managed with medications, both tremor response and satisfaction with medical therapy are highly variable. This review offers an overview of reports of the patient experience of tremor in early stage PD and current management options for this cardinal motor feature.